An insight into the sorption kinetics of boscalid onto soils: Effect of general soil properties. (June 2023) - Bhatt, Devesh; Srivastava, Anjana; Srivastava, P.C.
Abstract: Boscalid is a carboxamide fungicide widely used for crop protection, however owing to its high persistence, it is detected in high concentrations in various environments. Since the fate of such xenobiotics is strongly influenced by its interaction with soil components a better understanding of its adsorption onto soils of varying properties could allow the adjustment of its application in a given agro-ecological region to limit the consequent environmental burden. The present investigation was carried out to examine the kinetics of boscalid adsorption onto ten Indian soils of varying physico-chemical properties. Kinetic data of boscalid for all soils under investigation fitted well to both pseudo-first-order and pseudo-second-order kinetic models. However, based on the standard error of estimate (S.E.est. ) values pseudo-first-order model was better for all soil samples, except one soil which had the lowest readily oxidizable organic carbon. Adsorption of boscalid by soils appeared to be controlled by the diffusion-chemisorption process while for soils especially rich in readily oxidizable organic carbon or clay + silt content the intra-particle diffusion process seemed to be more important. Stepwise regression of kinetic parameters on soil properties revealed that the inclusion of a set of some soil properties could help better prediction of adsorbed amounts of boscalid and kinetic constants. These findings may help assess the fate and possible transport of boscalid fungicide in different soils. Graphical abstract: Image 1 Highlights: Soils with a higher content of clay + silt adsorbed more boscalid. Soils of higher sand content adsorbed less boscalid and reached equilibrium quickly. Pseudo-first order kinetics fitted best to the adsorption of boscalid for most soils. Intra-particle diffusion and diffusion-chemisorption well-predicted adsorption kinetics.